REAKSI PASAR SAHAM SYARIAH SELAMA PANDEMI COVID-19 DENGAN INFLASI SEBAGAI VARIABEL MODERASI - Siregar, Ihsan Mulia; Afandi, Ahmad (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2022)
The purpose of this study was to determine the effect of Covid-19 cases, interest rates and money supply on Sharia stock returns with inflation as a moderating variable. This research is a quantitative study using multiple regression analysis and using secondary data in the form of panel data on sharia stocks listed on the Jakarta Islamic Index (JII) starting from March 20, 2020 to July 2021. Sampling uses purposive sampling, which uses certain criteria so that can produce 20 companies listed in JII as a sample. The results show that the Covid-19 case has no effect on sharia stock returns, but interest rates have a significant and significant effect on sharia stock returns, then money supply has a negative and significant effect on sharia stock returns. Furthermore, inflation cannot moderate the Covid-19 case, interest rates and money supply on sharia stock returns. This research is expected to be useful for those who need information and references as a consideration in making decisions to invest.